Visual Power in Ancient Greece and Rome: Between Art and Social Reality - Hölscher, Tonio (University of California Press, 2018)
Visual culture was an essential part of ancient social, religious, and political life. Appearance and experience of beings and things was of paramount importance. In Visual Power in Ancient Greece and Rome, Tonio Hölscher explores the fundamental phenomena of Greek and Roman visual culture and their enormous impact on the ancient world, considering memory over time, personal appearance, conceptualization and representation of reality, and significant decoration as fundamental categories of art as well as of social practice. With an emphasis on public spaces such as sanctuaries, agora and forum, Hölscher investigates the ways in which these spaces were used, viewed, and experienced in religious rituals, political manifestations, and social interaction
Includes bibliographical references and index
Keywords: Rome -- Social life and customs; Greece -- Social life and customs; Visuelle Wahrnehmung; Römisches Reich; Griechenland